Instanton solutions in open superstring field theory - Berkovits, Nathan [UNESP]; Juliatto, Vilson Fabricio [UNESP]; Portugal, Ulisses M. [UNESP] (Springer Nature, 2022)
Open superstring field theory admits a “hybrid” formulation where N = 1 D = 4 supersymmetry is manifest for Calabi-Yau compactifications to four dimensions. Using this formulation, the half-BPS instanton solution of four-dimensional super-Yang-Mills can be easily generalized to the full open superstring field theory. In this paper, we compute the first stringy correction to the super-Yang-Mills instanton solution which involves turning on certain fields at the first massive level.
Keywords: Solitons Monopoles and Instantons; String Field Theory; Superstrings and Heterotic Strings